Search 74,114 tutors
FIND TUTORS
Ask a question
0 0

Show that 2[x-(2-3x)-4] is equal to x-5 when x=1.

Tutors, please sign in to answer this question.

1 Answer

Start with the innermost parentheses => (2-3x)
Plug in x and you'll get (2 - 3) which is (-1)
 
Proceed to the next level of brackets => [x - (-1) - 4]
Subtracting a negative is the same as adding the positive => [x + 1 - 4]
Simplify to [x + (-3)], since 1 - 4 is (-3). You could also just write [x - 3]
Plug in x and you'll get [1 - 3] which is (-2)
 
Don't forget the 2 outside the brackets
2 * (-2) = (-4)
 
Solve for the second function x - 5
Plug in x and you'll get 1 - 5 which is (-4)
 
(-4) = (-4) 
 
:D